2018
DOI: 10.1021/acsnano.8b00716
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Forces Guiding Staphylococcus aureus Cellular Invasion

Abstract: Staphylococcus aureus can invade various types of mammalian cells, thereby enabling it to evade host immune defenses and antibiotics. The current model for cellular invasion involves the interaction between the bacterial cell surface located fibronectin (Fn)-binding proteins (FnBPA and FnBPB) and the α5β1 integrin in the host cell membrane. While it is believed that the extracellular matrix protein Fn serves as a bridging molecule between FnBPs and integrins, the fundamental forces involved are not known. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 57 publications
3
43
0
Order By: Relevance
“…8 ). For integrins, injection of cRGD only reduces the binding frequency of ~1–2% on both cell types, which is in good agreement with the fact that integrins are mostly expressed on the bottom of the cell 26 . Altogether, these data obtained on cells by AFM represent to date the best evidence that S1–ACE2 complex is established in physiologically relevant conditions and underlines the complex situation with multiple cell-surface receptors accounting for the whole interaction.…”
Section: Resultssupporting
confidence: 81%
“…8 ). For integrins, injection of cRGD only reduces the binding frequency of ~1–2% on both cell types, which is in good agreement with the fact that integrins are mostly expressed on the bottom of the cell 26 . Altogether, these data obtained on cells by AFM represent to date the best evidence that S1–ACE2 complex is established in physiologically relevant conditions and underlines the complex situation with multiple cell-surface receptors accounting for the whole interaction.…”
Section: Resultssupporting
confidence: 81%
“…Recently, advanced AFM experiments with controlled surface chemistry enabled to resolve this discrepancy. The force required to separate staphylococcal FnBPA and SpsD adhesins (Prystopiuk et al, ) from Fn was shown to be extremely strong (~1,500–2,000 pN), a unusual mechanostability which originates from the β‐sheet organization of a tandem β‐zipper (Schwarz‐Linek et al, ). Upon binding to FnI modules, the intrinsically disordered binding sequences of the adhesins shift into an ordered structure by forming additional β‐strands along triple peptide β‐sheets in the Fn molecule.…”
Section: Bacterial Adhesins Engage In Ultrastrong Interactionsmentioning
confidence: 99%
“…A striking finding is that S. aureus cellular invasion involves protein bridges between bacterial adhesins and integrins on host cells that are extremely strong. Force spectroscopy experiments showed that FnBPA bind to Fn via a mechanically strong β‐zipper structure (∼1,500 pN), which further binds to α5β1 integrins with a strength much higher than that of the classical Fn−integrin bond (∼100 pN) (Prystopiuk et al, ). This suggests an activation mechanism in which Fn binding by FnBPA leads to the exposure of cryptic integrin‐binding sites via allosteric activation, which in turn engage in a strong interaction with integrins.…”
Section: Forces In Cellular Invasionmentioning
confidence: 99%
“…This interaction relies greatly on the extracellular matrix protein Fn that acts as a bridging molecule between FnBPs and integrins. Using singlecell and single-molecule experiments, Prystopiuk et al (2018) showed that FnBPA binds to Fn via a β-zipper-like structure, and this complex in turn enhances bacterial attachment to host cells through forming a strong link with the α5β 1 integrin.…”
Section: Intracellular Invasion Of Bacteriamentioning
confidence: 99%